The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1308/003588406x149183
|View full text |Cite
|
Sign up to set email alerts
|

The Extended Scope Physiotherapist in Orthopaedic Out-Patients – An Audit

Abstract: Ann R Coll Surg EnglThe aim of this study was to audit the activity of ESPs in our hospital. Benchmark standards were set as follows: (i) ESPs should independently assess 85% of patients appropriately referred to them; 2 (ii) the patient satisfaction rate should be 89%; 1 and (iii) no patient should be re-referred to an orthopaedic surgeon with the same complaint. Patients and Methods Extended scope physiotherapistsESPs had at least 5 years' clinical experience post qualification and at least 3 years' experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
59
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 5 publications
4
59
0
Order By: Relevance
“…2 Our study shows a higher proportion of independent management (92%) than for other services described in the literature (55-86%). 4,5,[17][18][19] The NUH ESP service was Did not attend consultationrelatively well established when this service evaluation was performed, which may mean that the ESPs had a greater understanding of the surgical reasoning process and were able to identify suitable surgical candidates more accurately because of increased training and experience. 14 Only 8% of all patients seen in the ESP service required input from a consultant.…”
Section: Discussionmentioning
confidence: 99%
“…2 Our study shows a higher proportion of independent management (92%) than for other services described in the literature (55-86%). 4,5,[17][18][19] The NUH ESP service was Did not attend consultationrelatively well established when this service evaluation was performed, which may mean that the ESPs had a greater understanding of the surgical reasoning process and were able to identify suitable surgical candidates more accurately because of increased training and experience. 14 Only 8% of all patients seen in the ESP service required input from a consultant.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported more extreme ranges. Pearse and colleagues, 50 who examined a large range of pathologies, noted that …”
Section: Discussionmentioning
confidence: 99%
“…(25)(26)(27) Only one of these studies compared treatment provided by an ESP and other professionals and this study was the first to describe an ESP service in an emergency department. (26) It was shown that 55% of patients were independently managed by the ESP and a follow-up suggested higher patient satisfaction with the ESP service.…”
Section: Discussionmentioning
confidence: 99%